High-Density Genetic Linkage Maps Provide Novel Insights Into ZW/ZZ Sex Determination System and Growth Performance in Mud Crab (Scylla paramamosain) - Waiho, Khor; Shi, Xi; Fazhan, Hanafiah; Li, Shengkang; Zhang, Yueling; Zheng, Huaiping; Liu, Wenhua; Fang, Shaobin; Ikhwanuddin, Mhd; Ma, Hongyu (Frontiers in Genetics, 2019)
Mud crab, Scylla paramamosain is one of the most important crustacean species in global aquaculture. To determine the genetic basis of sex and growth-related traits in S. paramamosain, a high-density genetic linkage map with 16,701 single nucleotide polymorphisms (SNPs) was constructed using SLAF-seq and a full-sib family. The consensus map has 49 linkage groups, spanning 5,996.66 cM with an average marker-interval of 0.81 cM. A total of 516 SNP markers, including 8 female-specific SNPs segregated in two quantitative trait loci (QTLs) for phenotypic sex were located on LG32. The presence of female-specific SNP markers only on female linkage map, their segregation patterns and lower female: male recombination rate strongly suggest the conformation of a ZW/ZZ sex determination system in S. paramamosain. The QTLs of most (90%) growth-related traits were found within a small interval (25.18 to 33.74 cM) on LG46, highlighting the potential involvement of LG46 in growth. Four markers on LG46 were significantly associated with 10 to 16 growth-related traits. BW was only associated with marker 3846. Based on the annotation of transcriptome data, eleven and two candidate genes were identified within the QTL regions of sex and growth-related traits, respectively. The newly constructed high-density genetic linkage map with sex-specific SNPs, and the identified QTLs of sex- and growth-related traits serve as a valuable genetic resource and solid foundation for marker-assisted selection and genetic improvement of crustaceans.